(untitled) (Open Herald: Periodical of Methodical Research, 2025)
The rapid advancement of digital technologies and artificial intelligence (AI) has significantly transformed business management practices across industries. Digital transformation is no longer limited to process automation but encompasses strategic innovation, data-driven decision-making, and the creation of sustainable competitive advantages. AI tools and algorithms enhance operational efficiency, optimize supply chain management, improve customer experience, and enable predictive analytics for risk management. This article explores the role of digital transformation and AI in reshaping business models, organizational culture, and leadership approaches. Special attention is given to challenges such as data privacy, ethical concerns, and the digital skills gap, which must be addressed to fully realize the potential of these technologies. The study emphasizes that companies adopting AI-driven strategies achieve higher resilience, adaptability, and long-term growth in an increasingly dynamic global market